Geometry-Aware Volume-of-Fluid Method - Cho, Junghyun; Ko, Hyeong-Seok (Computer graphics forum, 2013)
We present a new framework to simulate moving interfaces in viscous incompressible two phase flows. The goal is to achieve both conservation of the fluid volume and a detailed reconstruction of the fluid surface. To these ends, we incorporate sub‐grid refinement of the level set with the volume‐of‐fluid method. In the context of this refined level set grid we propose the algorithms needed for the coupling of the level set and the volume‐of‐fluid, which include techniques for computing volume, redistancing the level set, and handling surface tension. We report the experimental results produced with the proposed method via simulations of the two phase fluid phenomena such as air‐cushioning and deforming large bubbles.